Hubungan Sosial Ekonomi, Status Gizi dan Kepatuhan Konsumsi Tablet Zat Besi dengan Kejadian Anemia pada Ibu Hamil di Wilayah Kerja Puskesmas Kedaton Kota Bandar Lampung - Idfy Dwi Prayogo; Riska Wandini; Aprina Aprina (Malahayati Nursing Journal, 2025)
ABSTRACTThe incidence of anemia in pregnant women in Bandar Lampung City from January to November 2023, the highest anemia rate is in the Campang Community Health Center at 29.51%, the second is at the Kedaton Community Health Center at 28.54%, the third is at the Kedaton Community Health Center at 28 .54%, and fourth place at Sukamaju Health Center 23.71%. Objective to determine the relationship between socio-economic, nutritional status and compliance with the consumption of iron tablets with the incidence of anemia in pregnant women in the working area of the Kedaton Community Health Center, Bandar Lampung City in 2024. This research collects data using quantitative methods with a Cross Sectional Analytical Survey design. The sample in this study consisted of 45 respondents using a purposive sampling technique. The research instrument used the EasyToch GCHb type ET-321 Hb check tool and a questionnaire sheet. The results of this research were tested with statistical tests using the Chi Square test. There is a relationship between nutritional status and the incidence of anemia in pregnant women with a p-value of 0.000. There is a socio-economic relationship with the incidence of anemia in pregnant women with a p-value of 0.000. There is a relationship between adherence to taking Fe tablets and the incidence of anemia in pregnant women with a p-value of 0.000. There is a relationship between nutritional status, socio-economic status and adherence to consuming Fe tablets with the incidence of anemia in pregnant women. Keywords: Anemia, Pregnant Women, Related Factors  ABSTRAKAngka kejadian anemia pada ibu hamil di Kota Bandar Lampung pada bulan Januari sampai dengan November 2023, angka anemia tertinggi terdapat pada Puskesmas Campang sebesar 29,51%, urutan kedua Puskesmas Kedaton sebesar 28,54%, urutan ketiga pada Puskesmas Kedaton sebesar 28,54%, dan urutan keempat pada Puskesmas Sukamaju 23,71%. Diketahui hubungan sosial ekonomi, status gizi dan kepatuhan konsumsi tablet zat besi dengan kejadian anemia pada ibu hamil di wilayah kerja Puskesmas Kedaton Kota Bandar Lampung Tahun 2024.Penelitian ini mengumpulkan data dengan metode kuantitatif  dengan desain Survei Analitik pendekatan Cross Sectional. Sampel dalam penelitian ini berjumlah 45 responden dengan teknik pengambilan sampel secara Purposive Sampling. Instrumen penelitian menggunakan alat cek Hb EasyToch GCHb tipe ET-321 dan lembar kuesioner. Hasil penelitian ini diuji dengan uji statistik menggunkaan uji Chi Square. Terdapat hubungan status gizi dengan kejadian anemia pada ibu hamil dengan p-value 0,000. Terdapat hubungan sosial ekonomi dengan kejadian anemia pada ibu hamil dengan p-value 0,000. Terdapat hubungan kepatuhan mengonsumsi tablet Fe dengan kejadian anemia pada ibu hamil dengan p-value 0,000. Terdapat hubungan antara status gizi, sosial ekonomi dan kepatuhan konsumsi tablet Fe dengan kejadian anemia pada ibu hamil. Kata Kunci : Anemia, Ibu Hamil, Faktor-Faktor yang berhubungan